‘The organisation doesn’t particularly consider itself responsible for you’: organisational support for officers injured in the line of duty and organisational (in)justice - Bullock, Karen (Policing and society, 2020)
In times of increasing pressures on the police service, looking after the well-being of its staff has never been more paramount. However, there has been little academic consideration either of the nature of organisational support for officers injured in the line of duty, nor of the implications for injured officers and constabularies. This article aims to fill this lacuna by drawing on interviews with police officers in England and Wales to examine officers’ perceptions and experiences of organisational support following injury on duty. We report that in the context of perceptions of cynical attitudes of leaders regarding injury, the organisational devolution of responsibility for recovery to the officer, and in the limited nature of the provision of interventions designed to aid recovery, injured officers described how they lacked support, were dealt with inappropriately, and were approached unsympathetically and sceptically. This left officers feeling cut off in the aftermath of injury. The article contributes to the burgeoning literature on the role of organisational justice by providing insights into why fairness judgements are important to officers. We suggest that uncertainty and anxiety in the aftermath of injury was the prism through which organisational responses to their injury were interpreted by officers and found to be wanting. Police organisations therefore need to fully understand this process as a first step in developing improved policies and practices that provide the help and support officers need when they are injured and feeling especially vulnerable.